Centchroman versus Tamoxifen in the management of mastalgia: a randomized controlled clinical trial - S Khadka (Society of Surgeons of Nepal, 2016)
Introduction and Objective: Mastalgia is defined as painful nodularity for more than 1 week of menstrual cycle. The long list of drugs highlights the ongoing debate about the drug of choice for the management of mastalgia. So in this study, we compared the effectiveness and cost of Centchroman and Tamoxifen in the management of mastalgia.